Valor nutricional do feno das folhas de Cratylia Argentea na alimentação de coelhos em crescimento - CÂMARA, Bárbara (2017)
Considering that feed normally corresponds to 70% of the costs in an animal husbandry, the producer must search for raw materials that are able to reduce this cost, as long as they maintain or improve the zootechnical performance of the breeding. The rabbit requires high fiber content in the diet to maintain consistency and volume of the digesta, to ensure normal digestive transit, to distend the mucosa by stimulating intestinal motility and as a substrate for microbiota present in the cecum. Alfalfa hay is considered a balanced source of fiber, able to meet the nutritional requirements of the rabbit when it is included around 30% in the diet, but due to its high commercial value, it costs up to 40% the cost of the diet. Legume cratylia (Cratylia argentea) may be an alternative to the high added value of alfalfa hay, as it is a legume that normally has a nutritional value superior to that of most shrub legumes and contains only traces of tannins. The objective of this work was to evaluate the nutritional value of diets formulated with leaves each containing three leaflets with their respective stalks (petioles) of Cratylia argentea in the feeding of growing rabbits. A total of 28 New Zealand White rabbits (14 per treatment) with 55 days of age, of both sexes, were distributed in a randomized complete block design and two diets were evaluated. The reference diet was formulated to meet the requirements of the animals and the test diet was obtained by replacing 20% of the reference diet with the Cratylia argentea hay meal. The experimental period comprised 11 days, being seven days of adaptation and four days of total collection of feces, per experimental unit. The performance results (average daily weight gain, daily feed intake, feed conversion and final weight) were not influenced by the addition of hay from the leaves of the crattia. The coefficient of metabolizability of dry matter was better in the control group. The control group had higher consumption of crude protein, however, the group that fed the starch had higher excretion of crude protein in feces and lower percentage of crude protein retained. Cratylia argentea presents values of 1,400.67 kcal / kg of DM of digestible energy and 3.34% of digestible protein / kg of DM.